Numerical investigation of a dual cylindrical OWC hybrid system incorporated into a fixed caisson breakwater. (15th January 2023) - Yang, Can; Xu, Tingting; Wan, Chang; Liu, Hengxu; Su, Zuohang; Zhao, Lujun; Chen, Hailong; Johanning, Lars
Abstract: In this paper, a hybrid Oscillating Water Column (OWC)system combining with a heaving floater Wave Energy Converters (WEC) was investigated. The traditional cylindrical-type breakwater consists of dual cylinders with an opening inlet located at the outer wavefront wall, allowing a ring-type wave chamber formed between two cylinders. The oscillating buoy OB is hinged at the front of the OWC device. The WAVE Chamber formed between the two breakwater cylinders is to be used as OWC. Based on the Computational Fluid Dynamics (CFD) software Star CCM+, A three-dimensional numerical wave tank is developed to investigate the hydrodynamic performance of the hybrid system, and the numerical model is validated with published experimental results. The power take-off (PTO) damping performance and the hydrodynamic efficiency affected by water conditions and geometrical dimensions of the device are discussed. Results show that the after combining the floater to the breakwater-type WEC, a great improvement on frequency bandwidth was achieved and the efficiency increase to 83.28% compared to the case of a single device, which was of 57%. Furthermore, the effects of the opening inlet height and the volume ratio of the OWC chamber were studied to optimize the certain geometrical parameters. Lower height ratio of the opening inlet of the OWC chamber should be avoid for larger water depth condition while designing such a hybrid system. Highlights: An OWC-type breakwater with a heaving floater is put forward. The new hybrid system has good improvement on power extraction performance. The dual-cylindrical OWC can more effectively extract shorter waves and protect coast. Effect of geometrical properties and PTO damping on hydrodynamic efficiency are shown. Cost-sharing of integrated system can make WEC device economically competitive.